A Comparative Study on New Claim in the Appeal Process in Iranian and French Laws - syed hosein vaseghi; ghavam karimi; Mohamad Bagher Ameri nia (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2022)
The principle of prohibition of submitting a new claim in the appeal process is one of the governing principles in the court of appeals that is stipulated in Article 362 of the Code of Civil Procedure. Given the opposition between Articles 98 and 362 of the Code of Civil Procedure, it is essential to effectively investigate the matter. In view of the French Code of Civil Procedure, the mentioned principle is compared in the Iranian and French legal systems. A comparative study of the two legal systems indicates that Article 564 of the French Code of Civil Procedure and the two subsequent Articles, after mentioning the said principle, specify the exceptions by pointing out the criterion. The criteria mentioned in similar instances can be generalized to reach a united criterion to be applied. After mentioning the said principle as an instance, Article 362 of the Iranian Code of Civil Procedure states the exception and asserts that the said instances cannot be taken as criteria and the instances under Article 362 of the Iranian Code of Civil Procedure should be viewed exclusively, judicial procedure has not reached the unity of procedure and the deficiency shall be amended through enacting appropriate regulations